Production and characterization of monoclonal antibodies to a pilus colonization factor (colonization factor antigen III) of human enterotoxigenic Escherichia coli. - Honda, T (1989)
Three monoclonal antibodies (MAbs) to a pilus colonization factor (colonization factor antigen III [CFA/III]) of human enterotoxigenic Escherichia coli (ETEC) were developed and characterized. All of the MAbs isolated belonged to the immunoglobulin G2a subclass. The specificity of these MAbs for CFA/III pili was demonstrated by the immunogold-labeling technique. The presence of more than one epitope in CFA/III pili was suggested. One of the three MAbs appears to recognize a polymeric conformational epitope(s) of CFA/III. CFA/III antigenicity distinct from that of other pilus colonization factors of ETEC was demonstrated by both a bacterial agglutination test and a sandwich enzyme-linked immunosorbent assay using the MAbs. Of the 100 strains of ETEC isolated from persons with traveler's diarrhea, 8% were found to carry CFA/III pili. Two enzyme-linked immunosorbent assay systems which could detect as little as several or 50 ng of CFA/III per ml were developed.